COMPUTER GRAPHICS AT ELEMENTARY SCHOOL - DVORAK, Ondrej (Trends in education, 2010)
The paper is focused on problematics of computer graphics' teaching at elementary school. We are interested in computer programs, which are suitable for teaching at elementary school from several points of view. Research of actual situation of computer graphics' teaching at elementary school in Olomouc is a part of the paper.
Keywords: ICT; computer graphics; program; teaching; teacher.